Lingo Learn application as students' learning tool to enrich vocabulary: Students’ perspectives - Ramadhan Solin; Maryati Salmiah (Universitas Muhammadiyah Malang, 2025)
Lingo Learn is an English learning application that is free to use, easy to access. It offers an interactive language learning experience that can improve English skills and expand the vocabulary of its users. The main purpose of this study is to find out students' perceptions of the